2022
DOI: 10.1021/jacs.2c09672
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization Energies for Interfacial Proton-Coupled Electron Transfer to a Water Oxidation Catalyst

Abstract: The reorganization energy (λ) for interfacial electron transfer (ET) and proton-coupled ET (PCET) from a conductive metal oxide (In 2 O 3 :Sn, ITO) to a surface-bound water oxidation catalyst was extracted from kinetic data measured as a function of the thermodynamic driving force. Visible light excitation resulted in rapid excited-state injection (k inj > 10 8 s −1 ) to the ITO, which photo-initiated the two interfacial reactions of interest. The rate constants for both reactions increased with the driving fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 73 publications
2
27
1
Order By: Relevance
“…Furthermore, we employ this model to describe experimentally measured pH-dependent kinetic data for a representative interfacial electrochemical PCET reaction, namely, reduction of a Ru-based water oxidation catalyst attached to a tin-doped In 2 O 3 (ITO) surface. 19 Our model explains the origins of the previously observed weak pH dependence of PCET for this system using physically meaningful parameters. Moreover, our model's predicted behavior for a wider pH range is then confirmed by additional experiments.…”
Section: ■ Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Furthermore, we employ this model to describe experimentally measured pH-dependent kinetic data for a representative interfacial electrochemical PCET reaction, namely, reduction of a Ru-based water oxidation catalyst attached to a tin-doped In 2 O 3 (ITO) surface. 19 Our model explains the origins of the previously observed weak pH dependence of PCET for this system using physically meaningful parameters. Moreover, our model's predicted behavior for a wider pH range is then confirmed by additional experiments.…”
Section: ■ Introductionmentioning
confidence: 51%
“…When the pH increases from 3 to 5, the maximum rate constant only decreases by around 3-fold rather than decreasing 100-fold, as would be expected according to a model based on a single PCET pathway with H 3 O + as the proton donor, or being pH-independent, as would be expected according to a model based on a single PCET pathway with H 2 O as the proton donor. 19 Here, we focus on the PCET process associated with the reduction of the Ru III catalyst 37−44 attached to ITO. The two ET and two EPT channels, as well as Ox, OxH + , Red − , and RedH for this process, are depicted in Figure 3.…”
Section: Red (E) and K Imentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a recent study of a molecular water oxidation catalyst reported that a 0.19 Å change in a Ru−O bond length, for Ru III -OH → Ru II -OH 2 , corresponded to a λ i = 0.54 eV change in inner-sphere reorganization. 77 An inner-sphere reorganization energy of this magnitude would explain the unusually large total reorganization energy measured for this sensitizer.…”
Section: ■ Introductionmentioning
confidence: 89%